Associations between the Cervical Vertebral Column and Craniofacial Morphology - L. Sonnesen (Hindawi Limited, 2010)
Aim. To summarize recent studies on morphological deviations of the cervical vertebral column and associations with craniofacial morphology and head posture in nonsyndromic patients and in patients with obstructive sleep apnoea (OSA). Design. In these recent studies, visual assessment of the cervical vertebral column and cephalometric analysis of the craniofacial skeleton were performed on profile radiographs of subjects with neutral occlusion, patients with severe skeletal malocclusions and patients with OSA. Material from human triploid foetuses and mouse embryos was analysed histologically. Results. Recent studies have documented associations between fusion of the cervical vertebral column and craniofacial morphology, including head posture in patients with severe skeletal malocclusions. Histological studies on prenatal material supported these findings. Conclusion. It is suggested that fusion of the cervical vertebral column is associated with development and function of the craniofacial morphology. This finding is expected to have importance for diagnostics and elucidation of aetiology and thereby for optimal treatment.